A computational study on heterodimerization of charged porphyrins - ERDEM, SAFİYE (JOHN WILEY & SONS LTD, 2001)
The structures of the charged porphyrins and their dimers have been investigated with computational methods. Dimers have been formed based on electrostatic attraction of the opposite charges on two different porphyrin monomers, tetra ammonium porphyrin (TAP) and tetra carboxy porphyrin (TCP). Semi-empirical quantum mechanical calculations have been employed to explore the most stable ground-state structures of TCP, TAP and their hetero-dimers. Dimeric structures analyzed are all in face-to-face fashion indicating the strong electrostatic attraction between the two porphyrin rings. Calculations have also predicted that the protons transfer from -NH3+; groups to -COO- groups when the interplanar separation is shorter than 3.7 Angstrom. Copyright (C) 2001 John Wiley & Sons, Ltd.
Keywords: porphyrin dimerization; charged porphyrins; proton transfer; pi-stacking; quantum mechanical calculations; PI-PI-INTERACTIONS; METAL-METAL BONDS; CONFORMATIONAL BEHAVIOR; AQUEOUS-SOLUTION; HYDROGEN-BOND; GROUND-STATE; DIMERS; WATER; COMPLEXES; CHEMISTRY